pH-Dependent Thermal Stability of Vibrio cholerae L-asparaginase - Radha, Remya; Gummadi, Sathyanarayana N. (Protein and Peptide Letters, 2019)
Background: pH is one of the decisive macromolecular properties of proteins that significantly affects enzyme structure, stability and reaction rate. Change in pH may protonate or deprotonate the side group of aminoacid residues in the protein, thereby resulting in changes in chemical and structural features. Hence studies on the kinetics of enzyme deactivation by pH are important for assessing the bio-functionality of industrial enzymes. L-asparaginase is one such important enzyme that has potent applications in cancer therapy and food industry. Objective: The objective of the study is to understand and analyze the influence of pH on deactivation and stability of Vibrio cholerae L-asparaginase. Methods: Kinetic studies were conducted to analyze the effect of pH on stability and deactivation of Vibrio cholerae L-asparaginase. Circular Dichroism (CD) and Differential Scanning Calorimetry (DSC) studies have been carried out to understand the pH-dependent conformational changes in the secondary structure of V. cholerae L-asparaginase. Results: The enzyme was found to be least stable at extreme acidic conditions (pH< 4.5) and exhibited a gradual increase in melting temperature from 40 to 81 °C within pH range of 4.0 to 7.0. Thermodynamic properties of protein were estimated and at pH 7.0 the protein exhibited ΔG37of 26.31 kcal mole-1, ΔH of 204.27 kcal mole-1 and ΔS of 574.06 cal mole-1 K-1. Conclusion: The stability and thermodynamic analysis revealed that V. cholerae L-asparaginase was highly stable over a wide range of pH, with the highest stability in the pH range of 5.0–7.0.
Keywords: deactivation kinetics